Vesicular nucleotide transporter mediates adenosine triphosphate release in compressed human periodontal ligament fibroblast cells and participates in tooth movement-induced nociception in rats. (February 2020) - Mizuhara, Masahiro; Kometani-Gunjigake, Kaori; Nakao-Kuroishi, Kayoko; Toyono, Takashi; Hitomi, Suzuro; Morii, Aoi; Shiga, Momotoshi; Seta, Yuji; Ono, Kentaro; Kawamoto, Tatsuo
Highlights: Vesicular nucleotide transporter (VNUT) is expressed in periodontal ligament cells. Mechanical stress increased expression of VNUT mRNA in periodontal ligament cells. Mechanical stress increased ATP release from periodontal ligament cells. ATP release from the cells was reduced by clodronic acid, a VNUT inhibitor. Face-grooming behaviors in rats were reduced by administration of clodronic acid. Abstract: Objective: Pain control is imperative in orthodontic treatment. Adenosine triphosphate (ATP) is a key mediator released from periodontal ligament cells that excites nociceptive nerve endings. Vesicular nucleotide transporter (VNUT), encoded by the Solute carrier family 17 member 9 (SLC17A9) gene, participates in ATP uptake into secretory vesicles; thus, it may mediate tooth movement-induced pain. In the present study, we examined whether VNUT in periodontal ligament cells participates in tooth movement-induced nociception. Design: Expression levels of SLC17A9, connexin 43, and pannexin 1 in human periodontal ligament fibroblasts (HPDLFs) were examined by quantitative reverse transcription-polymerase chain reaction. Mechanical force via centrifugation-induced ATP release was measured using an ATP bioluminescence assay. Inhibitors were used to evaluate the role of ATP transporters. Face-grooming behaviors were assessed as indicators of nociceptive responses after experimental tooth movement in rats, as well as the effects of drugs for the pain-like behavior. Results: After HPDLFs underwent mechanical stimulation by centrifugation, SLC17A9 mRNA expression in the cells was significantly upregulated. Increased ATP release from HPDLFs after mechanical stimulation was suppressed by treatment with clodronic acid, a VNUT inhibitor, at concentrations of 0.1 and 1.0 μM. In rats, face-grooming behaviors (indicators of nociception) were significantly increased on day 1 after experimental tooth movement. Increased face-grooming behaviors were suppressed by systemic administration of clodronic acid (0.1 mg/kg). Conclusions: These results indicate that release of ATP from periodontal ligament cells via VNUT is important for nociceptive transduction during orthodontic treatment. Thus, VNUT may provide a novel drug target for tooth movement-induced pain.